ANALISIS GAYA BELAJAR PESERTA DIDIK KELAS VI A SD NEGERI SARIREJO - Nasiyatul Auliyah; Ikha Listyarini; Muhammad Prayito (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning style is a way of learning from how students absorb, and then organize and process the information obtained from the learning process. There are three types of learning styles that will be discussed in this study, namely visual (tend to learn through what they see), auditory (learn through what they hear) and kinesthetic (learn through movement and touch). This study aims to describe the learning styles of students in class VI A SD Negeri Sarirejo. This study uses a qualitative descriptive approach with the methods used are questionnaires, observations, and interviews. The results of the research are based on interviews, observations, and the results of the questionnaire given to 38 students, namely the learning style of class VI A students at Sarirejo State Elementary School is dominated by the visual learning style of a total of students. Followed by auditory learning styles and kinesthetic learning styles.